Design, synthesis, and biological evaluation of quinoxalinone derivatives as potent BRD4 inhibitors. (15th January 2023) - Xu, Kai-Yan; Wang, Xue-Ting; Cheng, Lei; Cui, Qi-Hang; Shi, Jian-Tao; Zhang, Li-Wen; Chen, Shi-Wu
Graphical abstract: Highlights: Novel quinoxalinone derivatives as BRD4 inhibitors were designed and synthesized. Compound X9 manifested promising BRD4 inhibitory activity (IC50 = 82.3 nM). Compound X9 exhibited superior anti-proliferative activity to HepG2 cell line. Compound X9 displayed good inhibitory effects on the migration and c-Myc protein in HepG2 cell line. Abstract: The bromodomain-containing protein 4 (BRD4) has gained growing interest as an effective drug target for the treatment of hepatocellular carcinoma (HCC). Herein, we designed and synthesized a series of quinoxalinone derivatives as BRD4 inhibitors via scaffold hopping. The representative compound X9 showed potent BRD4 inhibitory activity (with IC50 = 82.3 nM), and preferable antiproliferative activity against HepG2 cells (with IC50 = 1.13 ± 0.07 μM), as well as less toxicity against GES-1 cells (with IC50 = 57.24 ± 5.46 μM). Furthermore, compound X9 dose-dependently inhibited colony formation and blocked the migration of HepG2 cells by down-regulating the expression of Snail and MMP-9 while up-regulating the E-cadherin and Occludin. Besides, compound X9 efficiently down-regulated the expression of c-Myc in HepG2 cells, induced apoptosis, and arrested at G0 /G1 phase. In total, quinoxalinone was a potential core as BRD4 inhibitor and compound X9 might be effective for liver cancer therapy.